Matters of life and death : making moral theory work in medical ethics and the law - Orentlicher, David, 1955- (Princeton University Press, 2001)
Philosophical debates over the fundamental principles that should guide life-and-death medical decisions usually occur at a considerable remove from the tough, real-world choices made in hospital rooms, courthouses, and legislatures. David Orentlicher seeks to change that, drawing on his extensive experience in both medicine and law to address the translation of moral principle into practice--a move that itself generates important moral concerns. Orentlicher uses controversial life-and-death issues as case studies for evaluating three models for translating principle into practice. Physician-assisted suicide illustrates the application of ''generally valid rules,'' a model that provides predictability and simplicity and, more importantly, avoids the personal biases that influence case-by-case judgments. The author then takes up the debate over forcing pregnant women to accept treatments to save their fetuses. He uses this issue to weigh the ''avoidance of perverse incentives,'' an approach to translation that follows principles hesitantly for fear of generating unintended results. And third, Orentlicher considers the denial of life-sustaining treatment on grounds of medical futility in his evaluation of the ''tragic choices'' model, which hides difficult life-and-death choices in order to prevent paralyzing social conflict. Matters of Life and Death is a rich and stimulating contribution to bioethics and law. It is the first book to examine closely the broad problems of translating principle into practice. And by analyzing specific controversies along the way, it develops original insights likely to provoke both moral philosophers and those working on thorny issues of life and death.